Fikih kesehatan: Alasan darurat dalam telaah vaksinasi di masa pandemi - Wonda, Rocky Marcelino George; Amiruddin, Muhammad; Huwaida, Salma Aqila; Chairina, Azkia (Maliki Interdisciplinary Journal, 2025)
The COVID-19 pandemic has created a global health crisis that requires effective preventive measures such as mass vaccination. In Islam, vaccination must be evaluated based on Sharia principles, especially concerning halal status, necessity (adh-dharurah), and the objectives of Islamic law (maqāṣid al-syarī‘ah). This study examines the permissibility of vaccines from the perspective of Islamic health jurisprudence, focusing on the principle “al-dharurat tubih al-mahdhurat”—necessity permits the prohibited. Using a literature review of fatwas, MUI rulings, and contemporary fiqh sources, the study finds that vaccines containing non-halal elements are allowed if no halal alternatives exist and they serve to protect human life. The hifz al-nafs principle forms the foundation of this allowance. In conclusion, Islamic law is flexible and adaptive, providing solutions that prioritize public welfare and safety in emergency health situations.